Literature Review of the Impact of Multicurrency Regime On Financial Reporting - Wadesango N; Mellisa Jane Kucherera; Stephen Malatji; Lovemore Sitsha (Allied Business Academies, 2023)
The research sought to examine literature on the impact of Multicurrency regime on financial reporting. The research findings showed that, during the Multicurrency regime firms saw financial reporting becoming a challenge due to shifts in government policies which preclude them from reporting in accordance with prescribed standards such as IAS 21, failure to attract skilled staff with foreign currency exposure experience as well as failure to acquire multicurrency system tailored software. The research findings further established the best industry practises that firms can use, in case redollarization occurs in future. The study recommends firms to establish seminars and training programmes for the workforce carry out multicurrency diversification to hedge risks, make use of multicurrency programs to track exposure, consult regulatory boards and foreign currency specialists, and approach the government to work hand in hand when making monetary policies.